Premium auctions and risk preferences: an experimental study - Brunner, Christoph; Hu, Audrey Xianhua; Oechssler, Joerg (Games and economic behavior, 2014)
In premium auctions, the highest losing bidder receives a reward from the seller. This paper studies the private value English premium auction (EPA) for different risk attitudes of bidders. We explicitly derive the symmetric equilibrium for bidders with CARA utilities and conduct an experimental study to test the theoretical predictions. In our experiment, subjects are sorted into risk-averse and risk-loving groups. We find that revenues in the EPA are significantly higher when bidders are risk loving rather than risk averse. These results are partly consistent with theory and confirm the general view that bidders' risk preferences constitute an important factor that affects bidding behavior and consequently also the seller's expected revenue. However, individual subjects rarely follow the equilibrium strategy and revenue in our experiment is lower than in the symmetric equilibrium.
Gesehen am 04.09.2020